Produção de biocarvão e sua aplicação para a extração em fase sólida de agrotóxicos em água - Soares, Pâmela Ribeiro Lopes (2022)
The presence of pesticides in water bodies brings harm to animal and human health. To monitor these pesticides that are applied to various crops for pest control, solid phase extraction (SPE) methods with commercial and alternative adsorbents are used. In this sense, the work aims to produce and evaluate corn cob biochar as an alternative adsorbent in SPE for the determination of pesticides in water. Biochar was produced from pyrolysis (400°C, N2 flow 3 L min-1 ) with a yield of 42%. The granulometry was defined at 500 μm. Part of the material was activated with KOH (3 mol L-1 ) and HCl (3 mol L-1 ) to unclog and activate the pores. Biochars without activation (BSA) and with activation (BCA) were characterized. PCZ showed BSA (7,37) and BCA (6,07). FTIR was analyzed (BSA and BCA). The Boehm test showed acid groups (BCA). The EDX indicated the majority presence of silicon (BCA). SEM and BET showed porosity, with surface area (99,59 m2 g -1 ) and pore volume (0,265 cm3 g -1 ) for BCA. To analyze the adsorption capacity of pesticides in water (1 µg mL-1 ), SPE was performed with C18 and BCA. The best recoveries were obtained with acetonitrile (C18) and dichloromethane/methanol (50:50, v/v) (BCA). Pesticides were analyzed by Liquid Chromatography/Mass Spectrometry, using a C18 column and mobile phase consisting of water (5 mmol L-1 NH4HCO2) and methanol (5 mmol L-1 NH4HCO2). A 23 factorial design was performed to evaluate the variables (adsorbent, sample and eluent) for SPE with BCA. Among the 13 pesticides studied, 2,4-D, bifenthrin and carbosulfan were not recovered within the range established by ANVISA. Alachlor, ametrine, atrazine, diuron, flutriafol, imidacloprid, metolachlor, simazine, thiacloprid and thiamethoxam achieved recovery values between 75,9% and 117,8%. Statistical analysis was performed with Pareto Diagram, Response Surface and ANOVA and the best conditions were 100 mg of BCA, 50 mL of sample and 15 mL of eluent. However, elution with 5 mL also proved to be advantageous. Method validation was performed through linearity, sensitivity, selectivity, accuracy, precision, detection limit and quantification